Critique in German philosophy from Kant to critical theory - Acosta López, María del Rosario; McQuillan, J. Colin (Intersections (Albany, N.Y.), 2020)
"Critique has been a central theme in the German philosophical tradition since the publication of Immanuel Kant's Critique of Pure Reason. Some successors turned Kant's critique against itself and used it to challenge the authority of his system. Others extended his critique, applying it to aesthetics, epistemology, ethics, metaphysics, and political philosophy and generating new forms of criticism that were then taken up by Idealism, Romanticism, Marxism, Neo-Kantianism, Phenomenology, and Critical Theory. Yet these various legacies of Kantian critique are rarely brought into dialogue. Critique in German Philosophy seeks to address this problem by exploring the figures, works, movements, and philosophical subfields that have contributed to the development of the concept of critique in German philosophy, as well as their relation to one another. In so doing, it also challenges the standard ways philosophers have understood the task of philosophical critique. Attending to both canonical and previously overlooked texts and thinkers, the contributors bring to light alternative conceptions of critique in the German philosophical tradition with profound implications. In offering a critical revision of the history of modern European philosophy, the volume also raises new questions about what it means for philosophy to be "critical" today"--